DIFFERENCES IN DEMOGRAPHIC CHARACTERISTICS, RISKY BEHAVIOR AND HIV STATUS OF MEN AND WOMEN WHO WERE VOLUNTARILY AND CONFIDENTIALLY COUNSELED AND TESTED AT THE COUNSELING CENTER FOR HIV/AIDS OF THE INSTITUTE OF PUBLIC HEALTH IN BELGRADE - Stijovic, Vesna; Piperac, Pavle; Begovic, Biljana; Grujicic, Sandra (HEALTH CARE, 2021)
Introduction/Aim: Voluntary and confidential counseling and testing (VCCT) means getting information about HIV, ways of transmission, recognizing, reducing or avoiding risks for HIV infection, about safe sexual relations, the place where people can be tested, and what they should do depending on the test results in order to protect themselves and other people. The aim of this study was to examine differences in demographic characteristics, risky behavior and HIV status between men and women who were voluntarily and confidentially counseled and tested at the Counseling Center for HIV/AIDS of the Institute of Public Health in Belgrade.Methods: This research was conducted as a cross-sectional study and it included 3,480 persons (43.2% of women and 56.8% of men), who were counseled and tested at the Counseling Center for HIV/AIDS of the Institute of Public Health in Belgrade from 2017 to 2019. χ2 or Fisher’s test was used for the statistical analysis of data.Results: The majority of women (42.1%) and men (42.5%) who were counseled and tested were in the age group 21-30 years. Men used DPST services significantly more often than women. HIV positive status was significantly more frequent in men (2.5%) than in women (0.3%). Women came significantly more often to voluntary counseling and testing due to the possible exposure to HIV infection by heterosexual contact (84.9%), accident (11.1%) and raping (1.0%), while men were counseled and tested due to heterosexual contact (59.3%), homosexual and bisexual contact (33.6%) and intravenous drug abuse (1.1%). Men used condoms always or often (40.1%) and had two or more partners (53.2%) more frequently during the last 12 months in comparison to women (24.2% and 20.6%).Conclusion: Voluntary and confidential counseling and testing is necessary in the fight against HIV infection, especially from the perspective of early discovering of people with this infection and education of HIV negative persons about risky sexual behavior and possible prevention measures.
Keywords: voluntary, confidential counseling and testing, HIV/AIDS, risk factors